Effects of green manure intercropping and tillage on the fertility of irrigated dark-chestnut soil in a semi-arid climate - Hranovska, L.; Lykhovyd, P.; Reznichenko, N.; Bidnyna, I.; Kozyriev, V. (Regulatory Mechanisms in Biosystems, 2025)
Sustainable soil fertility management is crucial for maintaining agricultural productivity, particularly in semi-arid irrigated regions. This study aimed to evaluate the impact of tillage and fertilization systems, under continuous application of post-harvest residues and green manure intercropping, on the fertility of irrigated dark chestnut soil in a semi-arid steppe climate. The research was conducted through a two-factor field experiment within a four-field grain crop rotation system: winter barley with green manure intercropping – soybean – winter wheat with green manure intercropping – grain corn. The experiment followed a systematic design with three replications across a 12.5-hectare area at the Askaniiska Research Station (Kherson Region , Ukraine). Tillage treatments included a differentiated system (control), which alternated 12–14 cm disk tillage for cereals with deep plowing for row crops, and a long-term (13-year) no-till system with direct seeding. Fertilization treatments involved varying levels of nitrogen and phosphorus mineral fertilizers, combined with green manure crops: leaf mustard ( Brassica juncea ), buckwheat ( Fagopyrum esculentum ), annual white melilot ( Melilotus albus ), and lacy phacelia ( Phacelia tanacetifolia ). Soil samples from the 0–30 cm layer were collected annually and analyzed at the Institute of Climate-Smart Agriculture of NAAS with accordance to the standards of agrochemical soil analysis. Results indicated that green manure biomass yields were generally higher under differentiated tillage: leaf mustard – 12.38 vs. 8.46 t/ha; buckwheat – 11.97 vs. 10.74 t/ha; annual white melilot – 10.13 vs. 9.38 t/ha; and lacy phacelia – 14.47 vs. 13.25 t/ha (differentiated vs. no-till). The highest nitrogen and phosphorus content in biomass was observed in annual white melilot (on average, 2.62% and 0.76%, respectively), while buckwheat showed the hig h est potassium accumulation (2.81%). Green manure intercropping insignificantly changed soil NPK content in comparison to control. Significant difference was observed for potassium content only. The highest nitrogen content in the soil was recorded at the no-till and leaf mustard variant; the highest phosphorus content was at no-till and lacy phacelia; the highest potassium content was at no-till and lacy phacelia. As for the influence of tillage and fertilization on the crop rotation productivity, it was established that only tillage had significant impact on the indicator. Differentiated tillage was superior to no-till in this regard, providing the grain units yield higher by 11.67%. Statistical analysis underscores the benefits of the differentiated tillage system, especially when paired with higher fertilization levels and green manure, in enhancing the productivity of all studied crops. The Tukey HSD test confirmed significant differences between tillage-fertilization combinations, with differentiated tillage + N 120 P 40 + green manure consistently achieving the highest yields. No-till tended to result in lower yields, particularly under reduced fertilization levels. This supports the agronomic recommendation to combine differentiated tillage with nutrient-rich fertilization strategies for optimized crop performance. Overall, the integration of green manure intercropping into crop rotations accompanied by rationa l ly differentiated tillage proved to be an effective, environmentally sustainable, and agronomically sound strategy for maintaining soil fertility under irrigated conditions in semi-arid regions.